Inguinal Hernia Repair via Application of Mesh in Front of and behind the Fascia Transversalis - Bulbuller, Nurullah; Cetinkaya, Ziya; Kirkil, Cuneyt; Ayten, Refik; Aygen, Erhan; Girgin, Mustafa; Ilhan, Yavuz Selim (Springer India, 2014)
The aim of this study was to compare mesh placement in front of the fascia transversalis and behid the fascia transversalis via inguinal incision. We evaluated the results of 106 inguinal hernia cases treated with polypropylene mesh applied via the anterior approach between December 2004 and January 2010. Using the anterior approach, the mesh was placed preperitoneally behind the fascia transversalis in 51 of the patients, whereas in the other 55 patients the mesh was placed in front of the fascia transversalis. Mean duration of surgery was shorter in the patients in which the mesh was placed behind the fascia transversalis (60 min vs. 75 min) (P < 0.05). In all, 8 patients (7.5%) had postoperative complications, including hematoma (n = 4), seroma (n = 2), scrotal edema (n = 1), and orchitis (n = 1). There weren't any significant differences in the complication rate between the 2 groups of patients (P > 0.05). During a mean 44-month follow-up period (range: 12-72 months), no recurrence was observed. In conclusion, there weren't any significant differences between the 2 methods of inguinal hernia repair, other than the duration of surgery.
Keywords: Inguinal hernia; Anterior approach; Hernia repair with mesh